Using typologies to target private sector investments in gender equality and social inclusion in agrifood supply chains: Methodological guidance and good practices - Soto, Fernanda; Shijagurumayum, Meghajit; Elias, Marlene; Wiegel, Jenny; Morgan, Miranda; Nguyen-Perperidis, Emily; Ronchi, Loraine (2024)
This guide proposes a methodology to gain a deeper understanding of the diversity of participants involved in agrifood supply chains to enable companies to better target their investments in gender equality and women’s empowerment. The methodology builds on two approaches: intersectional and typological. An intersectional approach provides a nuanced understanding of how women and men in all their diversity experience disadvantage and privilege. A typological approach guides the creation of analytical groups of supply chain participants based on their characteristics to better understand their experiences within the supply chain and inform action at scale. This guide and the methodology on which it is based are designed for companies, NGOs, and others interested in enhancing gender equality in and the sustainability of supply chains.